OVERVIEW OF BSI DIGITALIZATION IN CREATING A HEALTHY COMPETITIVE MARKET BY OPTIMIZING EXISTING STATE-OWNED BANK CUSTOMERS - Alivia Fitriani Hilmi (Universitas Airlangga, 2021)
Indonesia has great potential for the development of the Islamic banking industry. However, the reality shows that this potential increase runs contrary to the development of Islamic banking. The concept of policies that have been set by the government has not been able to persuade the public to use Islamic banking. Therefore, the government implemented the latest policy, namely the merger of Islamic banks by providing one mobile banking. Where there is a merger of Islamic banks accompanied by digitalization, it automatically makes Indonesian Islamic banks a holding bank with larger capital, practical, efficient and easily recognizable. The merger of Islamic banks will strengthen the Islamic banking sector which is predicted to be able to move the real sector and have the highest assets. with the existing potential, the authors conducted research on the development of sharia bank customers by optimizing the digitalization of BSI with the potential for existing BUMN bank customers who have not used sharia services with a healthy competitive market. The research method used is SWOT analysis, as well as quantitative descriptive and simple linear regression T test withobservation data random sample. SWOT matrix analyzed the results also indicate one or mergers quadrant Islamic banks must maintain an aggressive strategy by leveraging the dominance of one bank BUMN.Selain existing customers, the result of quantitative descriptive analysis based on the calculation likert and intervalscale,72% of 60 respondents agreed to the item – a questionnaire item that refers to the creation of a healthy competitive market with the existence of BSI digital banking. From the results of the T test, it shows that there is an influence between the digitalization of banking mergers of Islamic banks on the optimization of existing customers of state-owned banks.